Analisis Asupan Gizi Makro dan Serat Pasien Diabetes Melitus Tipe 2 Komplikasi Dislipidemia yang Menjalani dan Tidak Menjalani Konseling Gizi - Listianasari, Yanita; Fatamorgana, Pijar Beyna; Nur, Edri Indah Yuliza (Universitas Tadulako, 2025)
Nutrition counseling is education for patients to maintain food intake according to needs. Adequate intake of macronutrients and fiber in patients with type 2 diabetes mellitus complicated by dyslipidemia is expected to maintain blood glucose control and lipid profile in good condition. The aim of this study was to determine the intake of macronutrients and fiber in patients with type 2 diabetes mellitus complicated by dyslipidemia at RSUD dr. Soekardjo Tasikmalaya who has undergone nutritional counseling and has never undergone nutritional counseling. This type of research was observational with descriptive analysis on 87 patients with type 2 diabetes mellitus complicated by dyslipidemia, namely 43 patients who had undergone nutritional counseling and 43 patients who had never undergone nutritional counseling. Sampling used purposive sampling technique. Data collection was carried out by filling out questionnaires on respondent characteristics (history of nutritional counseling, gender, age, education, employment, nutritional status) obtained by interview, anthropometric measurements (body weight and height) and intake of macronutrients and fiber with formula foods. 24 hour recall. The results of the study showed that macronutrient intake in patients who underwent nutritional counseling and who did not undergo nutritional counseling, including protein and carbohydrates, was included in the deficit category. Meanwhile, fat intake is included in the category above requirements. Fiber intake is included in the severe deficit category. This shows that there is a need to increase nutritional programs related to education for patients with type 2 diabetes mellitus with complications so that nutritional intake can be met according to needs with good dietary management.